COMPARATIVE ANALYSIS OF MUSICAL LEXICAL UNITS IN ENGLISH AND UZBEK: DIACHRONIC AND SYNCHRONIC PERSPECTIVES IN LINGUOCULTUROLOGY (Multidisciplinary Journal of Science and Technology, 2026)
This study investigates the national-cultural characteristics of musical lexis in English and Uzbek languages within the framework of linguoculturology. It analyzes how musical terminology reflects historical development, social values, and spiritual identity of each culture. The research employs comparative-typological, diachronic, synchronic, and componental analysis methods. The findings show that English musical terminology is more technical and globally standardized, while Uzbek musical lexis is deeply metaphorical and culturally rooted in maqom traditions and folklore. The study highlights semantic differences and cultural lacunae between the two systems, emphasizing the importance of cultural context in understanding musical language.